University English Teachers and Students’ Perceptions of Language Choices in EFL Classroom - Rahmah Julianti; Haryanto Atmowardoyo; Murni Mahmud (Universitas Negeri Makassar, 2016)
This research deals with university English teachers’ and the students’ perceptions regarding language choices used in the EFL classroom. This research involved two English lecturers and thirty two second semester students of English education in STKIP YPUP Makassar. This research applied qualitative approach. The data were collected via observation, interview and recording. The data obtained were analyzed in three phases, namely data reduction, data display and conclusion or verification. The result of the research showed that the lecturers preferred employing bilingual approach with the ideal language choice was English tended to be used less than Indonesian in the classroom. They did have language choices for the classroom interaction in which English was considered as the right choice for the lecturers in asking students’ feeling, praising, giving questions and directions as well as the students’ response for specific category while Indonesian was for joking, using the students’ idea, giving information, criticizing the students’ behavior and the students’ response for open-ended category. Surprisingly, the students’ language choices for this classroom interaction indicated the same preferences. However, they considered monolingual as important thing in English class yet still thought the need of Indonesian in which language rule was needed to apply. As a whole, they demanded more English exposure in the classroom interaction with inevitable allowance of Indonesian. Key words: Language choices, Perceptions, EFL classroom